2012
DOI: 10.1371/journal.pone.0033307
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne Outbreak of Gastroenteritis: Effects on Sick Leaves and Cost of Lost Workdays

Abstract: BackgroundIn 2007, part of a drinking water distribution system was accidentally contaminated with waste water effluent causing a gastroenteritis outbreak in a Finnish town.We examined the acute and cumulative effects of this incidence on sick leaves among public sector employees residing in the clean and contaminated areas, and the additional costs of lost workdays due to the incidence.MethodsDaily information on sick leaves of 1789 Finnish Public Sector Study participants was obtained from employers' registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…These authors reported a cost figure for sick leave without explaining how they had made the calculations. In a waterborne outbreak in Finland [36] information about costs for sick leave in public sector employees was obtained from the employers' registers that gave a very precise cost figure. However, by using this method information about sick leave for persons working outside the public sector was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported a cost figure for sick leave without explaining how they had made the calculations. In a waterborne outbreak in Finland [36] information about costs for sick leave in public sector employees was obtained from the employers' registers that gave a very precise cost figure. However, by using this method information about sick leave for persons working outside the public sector was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Further, utilities engaging in an improved water management practice are more likely to provide the type of water that has the trust of consumers (Contu et al 2005;Hrudey et al 2006), and this can impact on how policies and projects affecting the water supply are perceived (Doria 2010). While the financial burden incurred as the result of an outbreak of waterborne illnesses should be viewed as considerable enough to warrant that all available efforts to protect water safety have been taken (Corso et al 2003;Halonen et al 2012;Huovinen et al 2013), this remains a difficult link for some utilities, particularly among those where outbreaks have not previously occurred and motivation for change is limited (Hrudey 2011).…”
Section: Barriers To Implementing a Wspmentioning
confidence: 99%
“…For this reason, the WDS can often be a cause of concern due to the degradation and a potential source of contamination of water. There are many studies reported regarding the water quality failures . For example, Imran et al discussed the problems of red water release .…”
Section: Introductionmentioning
confidence: 99%